Putting Things in Order: Patterns of Trade Dynamics and Growth - Robert Feenstra; Pierpaolo Battigalli; Andrew K. Rose (University of California, Department of Economics, 1997)
We develop a procedure to rank-order countries and commodities using dis-aggregated American imports data. We find strong evidence that both countries and commodities can be ranked, consistent with the ""produce cycle"" hypothesis. Countries habitually begin to export goods to the United States according to an ordering; goods are also exported in order. We estimate these orderings using a semi-parametric methodology which takes account of the fact that most goods are not exported by most countries in our sample. Our orderings seem sensible, robust and intuitive. For instance, our country rankings derived from dis-aggregated trade data, turn out to be highly correlated with macroeconomic phenomenon such as national productivity levels and growth rates.
Keywords: 330